2018
DOI: 10.1016/j.ecss.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Spatial complexities in aboveground carbon stocks of a semi-arid mangrove community: A remote sensing height-biomass-carbon approach

Abstract: Mangroves are integral to ecosystem services provided by the coastal zone, in particular carbon (C) sequestration and storage. Allometric relationships linking mangrove height to estimated biomass and C stocks have been developed from field sampling, while various forms of remote sensing has been used to map vegetation height and biomass. Here we combine both these approaches to investigate spatial patterns in living biomass of mangrove forests in a small area of mangrove in northwest Australia. This study use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 46 publications
3
35
0
3
Order By: Relevance
“…The average height of Hainan Island's mangroves (6.99 m) is higher than the mean height of mangroves (~5.0 m) in the Everglades National Park, Florida, USA, reported by Simard et al [56], and greater than the mean height of mangroves (3.2 m) reported by Hickey et al [61] in northwest Australia. However, they are lower than the average height of mangroves (7.5 m) reported by Fatoyinbo and Simard [62] for all of Africa and significantly lower than the mangrove mean height (~21 m) in Papua, Indonesia, given by Asian et al [3].…”
Section: The Mangrove Height and Agb On Hainan Island And Comparison mentioning
confidence: 51%
“…The average height of Hainan Island's mangroves (6.99 m) is higher than the mean height of mangroves (~5.0 m) in the Everglades National Park, Florida, USA, reported by Simard et al [56], and greater than the mean height of mangroves (3.2 m) reported by Hickey et al [61] in northwest Australia. However, they are lower than the average height of mangroves (7.5 m) reported by Fatoyinbo and Simard [62] for all of Africa and significantly lower than the mangrove mean height (~21 m) in Papua, Indonesia, given by Asian et al [3].…”
Section: The Mangrove Height and Agb On Hainan Island And Comparison mentioning
confidence: 51%
“…Full waveform LiDAR is able to map three-dimensional (3-D) vegetation structures because it can penetrate the forest canopy [78], unlike passive optical sensors. Thus, LiDAR is effective when combined with optical data-i.e., Landsat 8 OLI [99], Rapid Eye [36], and SAR data-to map the canopy height and biomass of mangrove forests [79,100]. Several studies found the potential use of LiDAR and the Shuttle Radar Topography Mission (SRTM) global digital elevation model (DEM) for estimating the canopy height of mangrove forests [83,100] and tree height using calibration equations [101].…”
Section: Wavelength and Polarization Of Sar Datamentioning
confidence: 99%
“…Biomass estimation using airborne LiDAR can offer higher accuracy in tree extraction [154], tree height estimation [155], and AGB estimation [156] than those from radar and optical data [157], since LiDAR can characterize both horizontal and vertical canopy structures [130]. A recent study by Feliciano et al [99] used a terrestrial laser scanner (TLS) and a tripod mounted LiDAR to estimate the mangrove AGB in the western Everglades National Park in the United States (USA). A more recent study by Fatoyinbo et al [153] used airborne LiDAR to estimate mangrove AGB in the Zambezi Delta, Mozambique with R 2 values between 0.80-0.88 with a mean AGB value of 203 Mg ha −1 .…”
Section: Mangrove Biomass Estimation Using Lidar and Data Fusionmentioning
confidence: 99%
“…Both the ground points and non-ground points were utilized to generate the digital surface model (DSM) using the inverse distance weighted (IDW) interpolation method. The canopy height model (CHM) was produced through subtracting the DEM from the DSM [5]. Finally, the point clouds were normalized using the DEM subtraction method [26] and masked by the mangrove extent, which was produced from the WorldView-2 imagery.…”
Section: Uav Lidar Data and Mangrove Canopy Height Model Productionmentioning
confidence: 99%
“…Mangroves have attracted considerable attention due to their unique morphological characteristics and diverse eco-environmental service functions [1]. These services include coastal protection, biodiversity maintenance, and carbon sequestration [2][3][4][5]. The organic carbon in mangrove forests per unit area is four times higher than that of other terrestrial forest ecosystems [6].…”
Section: Introductionmentioning
confidence: 99%